Analisis Ekonomi Dalam Pembentukan Hukum - Azizah, Siti (FIAT JUSTISIA)
Indeed the legal establishment aspired by the 1945 Constitution is economic development and legal development that includes political and cultural development is also derived from the word "achieve sosial justice for all Indonesian peoples" is a form of justice in many respects. The complexity of economic problems, economic integration and technological nations in the trading process has a lot to make the laws contained in economic interest that so many laws actually lead to wrong interpretation by the general public so that the need for strict enforcement of government officials.